Design and Development of Goat Curry Packaging for Janthima Goat Farm, Phuket Province - Paladsongkhram, Ruethamrong; Phutkhao, Phruetthiphong; Pramnachot, Monthita; Rongkul, Phahol; Japrung, Janthima (Area Based Development Research Journal, 2019)
The agencies under Ministry of Science and Technology collaborate with Phuket Rajabhat University to maximize the potential of OTOP entrepreneurs through integrated academic - business cooperation in goat products packaging design and development in Phuket province. The cooperation is based on problems and demand of entrepreneurs. The objectives of the research are to investigate the community problems, look for solutions, and develop and design packaging that can prolong the product shelf life. The outcome is packaging that is suitable for the products in terms of safety, cost, efficiency, and function. Community participation plays a role in identifying product uniqueness and branding. The research employs mixed methods of qualitative and quantitative approaches to create brand identity and develop goat curry packaging of Thalang district, Phuket province. Investigation of problems reveals that “Janthima goat farm” is located in a Muslim community, raising meat goat for distribution with an aim to increase income by selling goat curry during festivals and events. However, its previous packaging does not attract consumers and is not of standard by the lack of product details on the label. Additionally, the packaging tends to result in short shelf life. Therefore, the researchers and the entrepreneur have studied the guideline for the development and identity of brand, trademark, and label and packaging of goat curry that will reflect the identity and happiness of goat raising, from the quality goat meat raising in the caring farm to “Janthima goat farm” curry goat product. The outcome is “Janthima goat farm” package in red brown and viridian PP hard plastic cup that can be pasteurized and keep goat curry at the temperature lower than 4°C. Further tests on the product show that 10-day storing at the accelerated condition under pH of 6.21 - 6.79 leave the product in good condition without contamination. The satisfaction towards the packaging is found at the highest level. Thus, the model has been produced and delivered to the commercial market.